2017
DOI: 10.1111/acer.13483
|View full text |Cite
|
Sign up to set email alerts
|

The Glycine Receptor—A Functionally Important Primary Brain Target of Ethanol

Abstract: Identification of ethanol's (EtOH) primary molecular brain targets and determination of their functional role is an ongoing, important quest. Pentameric ligand-gated ion channels, that is, the nicotinic acetylcholine receptor, the γ-aminobutyric acid type A receptor, the 5-hydroxytryptamine , and the glycine receptor (GlyR), are such targets. Here, aspects of the structure and function of these receptors and EtOH's interaction with them are briefly reviewed, with special emphasis on the GlyR and the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 235 publications
(310 reference statements)
0
36
0
Order By: Relevance
“…Interactions and co‐occurrence of extracellular levels of taurine following ethanol administration are a known phenomenon, whereas we demonstrated that in order for ethanol to raise dopamine levels, a concomitant ethanol‐induced increase of extracellular taurine is required . Ethanol and the concomitant elevation of taurine activate a neuronal circuitry that results in increased dopamine output in the nAc (reviewed in Söderpalm et al). This circuitry was also found to be of functional importance with regard to voluntary ethanol intake in the rat .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Interactions and co‐occurrence of extracellular levels of taurine following ethanol administration are a known phenomenon, whereas we demonstrated that in order for ethanol to raise dopamine levels, a concomitant ethanol‐induced increase of extracellular taurine is required . Ethanol and the concomitant elevation of taurine activate a neuronal circuitry that results in increased dopamine output in the nAc (reviewed in Söderpalm et al). This circuitry was also found to be of functional importance with regard to voluntary ethanol intake in the rat .…”
Section: Introductionmentioning
confidence: 68%
“…In order to reduce the prevalence of alcoholism and improve current treatments for alcohol use disorders (AUDs), an increased understanding of the mechanisms underlying excessive ethanol intake is needed. Since addictive drugs in general increase dopamine activity in the mesolimbic dopamine system, an effect linked to their rewarding and reinforcing properties, much research has been aimed at elucidating the mechanisms by which addictive drugs, including ethanol, increase dopamine. Furthermore, although it is of importance to understand mechanisms underlying ethanol's ability to activate the brain reward pathways in naïve animals, studies of ethanol‐consuming animals are needed in order to disclose tentative neuronal adaptations following long‐term alcohol exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol (30-100 mM) acts also on ligand-gated ion channels (LGICs; Dildy-Mayfield et al, 1996;Mascia et al, 1996). For example, ethanol can potentiate the function of LGICs such as glycine and GABA A receptors and inhibit excitatory NMDA and AMPA glutamate receptors in brain regionand concentrationdependent manner (Lovinger & Roberto, 2010;S€ oderpalm et al, 2017). Canonical activation of ionotropic glutamate receptors (NMDA and AMPA) on VTA DA neurons increases in vivo firing and burst activity ( Fig.…”
Section: Primary Ethanol Modulation Of Vta Da Neuronsmentioning
confidence: 99%
“…Research in the last years identified numerous direct molecular targets of ethanol in the brain, including ligand-gated ion channels (e.g. NMDAR (Kuner, Schoepfer andKorpi 1993, Lovinger, White andWeight 1989); GABAAR (Marszalec et al 1994); GlyR (Soderpalm, Lido and Ericson 2017); nAChR (Cardoso et al 1999); others (Dopico and Lovinger 2009)), potassium channels (e.g. BK channels (Dopico, Bukiya and Martin 2014); GIRK channels (Bodhinathan and Slesinger 2013)), sodium channels (Horishita and Harris 2008), enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%